Intangible Cultural Heritage in Religious Contexts: a Comparative Legal Study - Thiago Rafael Burckhart (Pensar, 2025)
This article aims to analyze the interconnections between tangible and intangible religious heritage, by underlining the role of intangible cultural heritage (ICH) legal instruments, such as safeguarding measures, in improving the protection of its associated heritage: the “tangible” dimension of religious spaces. To that end, a comparative empirical analysis is conducted on the elements inscribed in the ICH UNESCO list database from Southern Europe, focusing on the implemented safeguarding measures described both in Nomination Files and Periodic State Reports. The analysis is grounded on the field of comparative public law and public international law, and addresses an interdisciplinary perspective between legal and political science, with a focus on law and policy enforcement. The article analysis the legal definition of ICH; dives into the concepts of religious heritage and religious spaces; and then, analyses how ICH instruments can foster sustainability in religious spaces, through safeguarding measures.